99. Auditory event-related potentials (ERPs) evoked by human syllables, musical notes/chords and animal sounds in pre-school children with specific expressive language disorders (SELDs) for assessing the selectiveness of auditory processing. Issue 4 (April 2016) - Scaioli, V.; Granocchio, E.; Curzi, S.; Alverà, S.; Airaghi, G.; Musso, G.; Magazù, S.; Pesce, I.; Sarti, D.; Giacomelli, S.; Molteni, B.
Abstract : Auditory ERP recordings are a useful neurophysiological means of assessing the temporal domain of the pre-linguistic and linguistic sensory deficits involved in expressive specific language impairment (SLI). We recorded auditory ERPs in 32 pre-school children aged 3–5 years with SLI before they underwent a rehabilitation programme. The ERPs were evoked using syllables (SyERPs), music (MuERPs) and animal sounds (AnERP) chosen from among those used in the trials carried out before, during and after an intensive rehabilitation programme in order assess: (a) the quality of ERP abnormalities; (b) the selectiveness of the ERP changes associated with the three types of stimuli; and (c) the changes induced by the rehabilitation programme. The SyERPs and MuERPs gave rise to four components (in P1, N1, N2 and P2) classified on the basis of their latency and polarity; the AnERPs only gave rise to P1 and N1 components. The ERPs had both common and distinctive features in terms of their waveforms and topographical distribution: the SyERPs were more left lateralised, and the MuERP more right lateralised. Later negative components were also recorded depending on the type of stimulus. In comparison with controls, P1 and P2 SyERPs were the most abnormal. As the rehabilitation led to selective SyERP changes, these may be useful for diagnosis and monitoring SLI.